Effects of Sodium Chloride on the Rheological Properties, Setting Time, Self-desiccation and Strength of Cemented Paste Backfill - Carnogursky, Elizabeth Alexandra (Université d'Ottawa / University of Ottawa, 2023)
Cemented paste backfill (CPB) is a highly advantageous method of backfill that has been increasing in use in recent decades as it provides many environmental, economic, and practical benefits. When combined with cement and water, it recycles a portion of the dewatered tailings produced from mines as backfill for underground stopes. CPB is transported from the plant on the surface through pipes to the stopes, sometimes over several kilometers, and then placed in underground mining cavities (stopes) to support the ground or rock mass. Therefore, it must meet certain rheological, setting time, and strength gain performance requirements. Additionally, as many mines around the world are located in areas of freshwater scarcity, and societies are holding corporations to ever higher standards for humanitarian and environmental responsibility, many mines are seeking to utilize locally available, saline groundwater or seawater as mixing water in backfill. The impacts of this decision on the rheological, setting, and strength properties of CPB must be better understood to allow for the confident selection of this convenient solution, as the risks associated with improper design include huge costs due to pipeline clogging and death or injury due to backfill failure and ground subsidence. NaCl is a contributor to natural groundwater and seawater salinity and may be present in concentrations of up to 300 g/L. An additional cost-saving measure favoured by mines is to replace some of the costly Portland cement with much cheaper supplemental cementitious materials such as blast furnace slag. Therefore, this thesis examines the impacts of NaCl concentration and binder composition on the yield stress, viscosity, initial and final setting time, and strength development of CPB. A robust experimental program has been undertaken in which CPB was subjected to the above-mentioned tests in addition to pH and MIP testing, SEM, TG/DTG, XRD, and zeta potential analyses, and electrical conductivity, suction, and water content monitoring. CPB samples were made with synthetic silica tailings, Portland cement, and water with NaCl concentrations of 0 g/L, 10 g/L, 35 g/L, 100 g/L, and 300 g/L and CPB made with 35 g/L and slag replacement percentages of 0%, 25%, 50%, and 75%. Additional samples tested were made with natural gold tailings, Portland cement, and NaCl concentrations of 0 g/L and 35 g/L for verification. Rheological testing was conducted at 0 minutes, 15 minutes, 1 hour, and 2 hours after mixing, and UCS testing was conducted after 1 day, 3 days, 7 days, 28 days, and 60 days of curing. Additional tests or analyses were performed on selected mixes and curing times for optimum insight and monitoring was conducted from 0 to 28 days after curing. It was found that low concentrations of NaCl (10 g/L and 35 g/L) generally had favourable impacts on the UCS and setting times of CPB, while higher concentrations had negative impacts. The impacts of slag replacement on UCS development of saline CPB were also generally favourable. However, the impacts of slag replacement on initial setting time were generally negative, and favourable at higher replacements (50% or more) for final setting time. Low NaCl concentration led to slightly negative impacts on yield stress, especially at longer curing times (1-2 hours), but high concentrations greatly reduced the yield stress. NaCl concentration had minor impacts to viscosity, with any concentration leading to a slightly higher initial viscosity but slightly lower viscosity at longer curing times. Slag replacement content had negligible effects on yield stress, but led to favourable decreases in viscosity over longer curing times. The combination of positive and negative impacts indicates that care must be taken to knowledgeably prioritize or balance critical properties in mix design, though there is indication of opportunities for overall improvement. Supplemental testing provided useful information to explain the mechanics behind the results which will allow designers to carefully select the required components for the desired properties.
Keywords: Cemented Paste Backfill; Rheology; Strength; Self-desiccation; Setting time; Sodium Chloride